Does a Preoperative Educational Class Increase Patient Compliance. (September 2015) - Kim, Kelvin; Chin, Garwin; Moore, Tyler; Schwarzkopf, Ran
Past studies have shown successful outcomes regarding the use of various interventional education methods in improving patient compliance. At our institution, different educational resources are offered and encouraged, including a 2-hour–long educational class, to prepare patients who are undergoing total joint arthroplasty procedures. Given the significant impact that patient compliance with preoperative instruction can have on overall outcomes of these procedures, this study was intended to assess the effects that the educational classes can have on patient compliance with this institution's 6-point preoperative total joint arthroplasty protocol. The study analyzed 2 groups, those who did and did not attend the preoperative classes, and compliance rates were compared between the 2. It was hypothesized that patients who did attend the classes would be more compliant to the protocol compared to those who did not. Although results from the study showed that there were no significant differences in adherence between the 2 groups, future quality assessment studies can build off this in order to move toward achieving optimal patient compliance with preoperative instructions.